Sexual harassment at work: Design of a new questionnaire to measure sexual harassment. (13th November 2019) - Nielsen, M B D; Madsen, I E H; Clausen, T; Skov, S S; Kjær, S; Kvorning, L V; Aldrich, P T; Rugulies, R; Folker, A P
Abstract: Background: Sexual harassment is a complex phenomenon and our knowledge is hampered by a lack of consensus on the definition and measurement. However, workplaces need reliable instruments that provide a nuanced understanding of sexual harassment and input for action to mitigate negative consequences. The aim of this project is to help workplaces prevent and manage sexual harassment, which include developing a new and comprehensive instrument to monitor sexual harassment (Inventory of Workplace Sexual Harassment). In this abstract, we explain the process of designing the questionnaire. Methods: The design process follows three steps: (1) Identification of a theoretical and conceptual framework, (2) item development and (3) field testing. First, we identified relevant theoretical and conceptual frameworks, which we discussed with an expert group consisting of researchers and stakeholders (employer and trade unions). Second, we developed items based on expert inputs and previous surveys. We adapted the first version of the questionnaire following a feedback round with the expert group. Third, we will complete field testing in 2019-2020. Field testing encompasses cognitive interviews (n = 15) and in-depth interviews with men and women exposed to sexual harassment to assess clarity and relevance (in 2019), and a pilot study at 15 workplaces to assess prevalence and usability (in 2020). Results: Based on the theoretical and conceptual model from Fitzgerald et al, we developed a preliminary version, consisting of 22 items that cover three domains: (1) unwanted sexual attention, (2) gender harassment and (2) sexual coercion. The survey draws on questions from SEQ-DoD and Bergen Sexual Harassment Scale. Results from field testing will be available for the conference. Conclusions: The Inventory of Workplace Sexual Harassment will provide a comprehensive and validated measurement of workplace sexual harassment and will help workplaces prevent and manage sexual harassment. Key messages: Sexual harassment is a complex and multifaceted phenomenon, but our knowledge is hampered by a lack of consensus on the definition and measurement. This study contributes with a new instrument measuring the prevalence of workplace sexual harassment and tools for prevention and management of sexual harassment.